Enhancement of absorption of tetramethylpyrazine by synthetic borneol - CHEN Tie-feng; LIN Shu-guang; CHEN Lu-xi; JIANG Gui-fen; LIANG Zhao-yan; YANG Ming; QIAN Yi-zhi; XIE Yan-ai (Acta Pharmacologica Sinica; Vol 11, No 1 (January 1990): Acta Pharmacologica Sinica, 2016)
Sprague-Dawley rats were given ig tetramethylpyrazine phosphate (TMP) 5 mg/kg with or without previous borneol 5 mg/kg. The plasma TMP concentrations were analysed by GC method, and the data were treated by NONLIN program. The Cmax were 931 and 562 ng/ml, respectively, (P less than 0.01); while the AUC were 68,849 and 37,174, respectively, (P less than 0.05). It is suggested that the borneol enhances the absorption of the TMP but not in elimination.